UNRAVELLING ECONOMIC AND SOCIAL INEQUALITY: A LITERATURE REVIEW OF ITS CAUSES AND IMPACTS - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Economic and social inequality in Indonesia has become an increasingly serious problem in recent decades. This article aims to examine the causal factors and impacts of such inequality through a literature review. The results show that economic and social inequality is caused by various interrelated factors, such as differences in access to economic resources, the quality of infrastructure and public services, the taxation system and government spending, the quality of human resources, as well as the political situation and economic policies that are less favourable to the interests of the lower classes. These factors reinforce each other and create a vicious cycle of poverty that is difficult to break. Widening inequality is detrimental to social stability, economic growth, and human development. Widening inequality can trigger social conflict, hamper purchasing power and aggregate demand, and make it difficult for the poor to access basic services such as education and health. Efforts to reduce inequality are crucial in order to maintain social harmony, promote more inclusive economic growth, and realise justice and prosperity for all. Therefore, comprehensive and sustainable efforts are needed to address the root causes of inequality, through policies that promote equitable economic and social access, improve the quality of human resources, and reform the tax system and government spending that is more pro-people. Only then can Indonesia realise a more just and equitable development for all people.